2020
DOI: 10.1016/j.molmet.2020.101040
|View full text |Cite
|
Sign up to set email alerts
|

Roles of bone-derived hormones in type 2 diabetes and cardiovascular pathophysiology

Abstract: Background Emerging evidence demonstrates that bone is an endocrine organ capable of influencing multiple physiological and pathological processes through the secretion of hormones. Recent research suggests complex crosstalk between the bone and other metabolic and cardiovascular tissues. It was uncovered that three of these bone-derived hormones—osteocalcin, lipocalin 2, and sclerostin—are involved in the endocrine regulations of cardiometabolic health and play vital roles in the pathophysiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 162 publications
(321 reference statements)
0
23
0
2
Order By: Relevance
“…Scientific evidence confirmed that OC is involved in multiple biological processes, including energy metabolism, cognition, stress response, CV health. These physiological functions have been documented to be regulated by both OC forms, cOC and ucOC [186]. OC can bind to neurons of the hippocampus, brainstem, or midbrain, and enhance the production of monoamine neurotransmitters, prevent anxiety and depression, and support learning and memory.…”
Section: The Effect Of Vitamin K On Neurodegenerative Diseasesmentioning
confidence: 99%
“…Scientific evidence confirmed that OC is involved in multiple biological processes, including energy metabolism, cognition, stress response, CV health. These physiological functions have been documented to be regulated by both OC forms, cOC and ucOC [186]. OC can bind to neurons of the hippocampus, brainstem, or midbrain, and enhance the production of monoamine neurotransmitters, prevent anxiety and depression, and support learning and memory.…”
Section: The Effect Of Vitamin K On Neurodegenerative Diseasesmentioning
confidence: 99%
“…Animal and in vitro studies showed the protective effect of unOCN on vessels. This was explained by the enhanced expression of endothelial nitric oxide synthase (eNOS) and nitric oxide (NO) production [14]. Lower serum OCN concentration was found among hypertensive men, but not women.…”
Section: Discussionmentioning
confidence: 99%
“…Total OC (tOC), which is a combination of circulating ucOC and cOC, is more often reported because it is easier to measure. ucOC is thought to be the bioactive form of OC, involved in the regulation of glucose homeostasis and energy metabolism ( Figure 1 ) [ [3] , [4] , [5] , [6] , [7] ]. This has led some to suggest that ucOC may be a future therapeutic target for metabolic diseases, such as insulin resistance and diabetes [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%